The Impact of Competition on “Make-or-Buy” Decisions: Evidence from the Spanish Local TV Industry - Gil, Ricard; Ruzzier, Christian A. (Management Science, 2018)
This paper empirically investigates whether changes in product market competition affect firm boundaries. Exploiting regulation-induced shocks to entry barriers and differences in regulation enforcement across cities to obtain exogenous variation in competition, we establish a negative causal effect of competition (through reduced entry barriers and a larger number of rival firms) on vertical integration in the setting of the Spanish local television industry between 1995 and 2002. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2016.2633 . This paper was accepted by Bruno Cassiman, business strategy.